ANALISIS TERHADAP RETURN SAHAM SYARIAH MELALUI EMPAT INDIKATOR TEKNIKAL DI JAKARTA ISLAMIC INDEX - NOFRIANTO NOFRIANTO; IVALAILI IVALAILI (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This study aimed to discover the effectiveness of four technical indicators, namely, Moving Average, Relative Strength Index (RSI), Bollinger Bands, and Moving Average Convergence Divergence (MACD) in predicting stock returns in the Jakarta Islamic Index. This study used a qualitative approach using descriptive methods. Based on the results of the analysis, it was found that the Bollinger Bands indicator has a more optimal return rate compared to the Moving Average, RSI, and Moving Average Convergence Divergence (MACD) indicators. In addition, the Bollinger Bands indicator has proven to be more optimal in its use to see transaction signals. For the results given, the technical indicators were higher than the moving average indicator, RSI and MACD, especially for stocks that had a fairly high level of range and volatility, so that in use this indicator can determine the existence of a sufficiently good upper and lower limit so that there was no buying shares at too high price or selling shares at too low a price.